Introduction to Hall (1988) Theoretical comparison of bootstrap confidence intervals - Mammen, Enno (Breakthroughs in Statistics, 1997)
Bootstrap was introduced in Efron (1979) [for a reprint with discussion see also Volume II of Kotz and Johnson (1992)]. For a long time it was one of the most active fields in mathematical and applied statistics. It has been discussed for a variety of statistical applications. Now we have a clear and detailed knowledge on the advantages and restrictions of the bootstrap approach. Bootstrap has become a standard method in the tool kit of statisticians. Some books on bootstrap [Beran and Ducharme (1991), Hall (1992), Mammen (1992), Efron and Tibshirani (1993), and Shao and Tu (1995)] have appeared already. Bootstrap has found its way into introductory text books on statistics.
Gesehen am 22.02.2018